2006
DOI: 10.1007/s00381-006-0240-2
|View full text |Cite
|
Sign up to set email alerts
|

A mature cystic teratoma in pineal region mimicking parietal encephalocele in a newborn

Abstract: A mature cystic teratoma mimicking parietal encephalocele is extremely rare. Germ cell tumors should be kept in mind in the differential diagnosis of all midline lesions with unusual radiographic appearance. Cerebral venous angiography or MR angiography must be performed for the diagnosis and the surgical planning in lesions located near SSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…In our study, five lesions (83%) contained multiple patchy and/or punctuate calcification in six patients who underwent CT evaluation. Our CT findings and previous findings (3,(6)(7)(8) were in accordance regarding the presence of calcification and fatty tissue, which are typical dominant features of intracranial teratomas.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, five lesions (83%) contained multiple patchy and/or punctuate calcification in six patients who underwent CT evaluation. Our CT findings and previous findings (3,(6)(7)(8) were in accordance regarding the presence of calcification and fatty tissue, which are typical dominant features of intracranial teratomas.…”
Section: Discussionsupporting
confidence: 90%
“…Clinically, the incidence of teratomas increases as age decreases (7). Several publications have reported that intracranial teratomas present between 1 and 46 years of age (mean age, 14.8 years), and have a male predominance (male-to-female ratio, 28:3) (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Although the pineal gland is a common location for intracranial germ cells and epidermoids ($ 40-50%), dermoids are not commonly observed in this area. 7,8 Patients with dermoid cysts are usually asymptomatic, although they may present symptoms related to local mass effect, seizures, or recurrent meningitis. 9 On computed tomography (CT) scans, dermoid cysts usually appear as rounded, well-circumscribed, non-enhancing, hypodense lesions.…”
Section: Introductionmentioning
confidence: 99%